ANALISIS DAMPAK KEBERADAAN USAHA HIBURAN LOKALISASI KM 10 TERHADAP USAHA LAIN DI KAMPUNG KADUN JAYA - Albertin Limbu; Imanuel Kartika, Antje Tuasela (Adisam Publisher, 2024)
This study aims to analyze the impact of the existence of localized entertainment businesses at Km 10 on other businesses in Kadun Jaya Village. The analysis method used is the Multiplayer Eflect to identify and evaluate the economic impact of the existence of localized entertainment. Data were collected through surveys and interviews with business owners and the local community. The results of the study indicate that the existence of localized entertainment at Km 10 has a significant impact on other businesses in Kadun Jaya Village, both positively. These impacts include changes in consumption patterns, expenditures, and community perceptions of the surrounding environment. The implications of these findings are expected to provide input for policy makers in formulating sustainable and inclusive regional development strategies.